FORMULA BINET DAN JUMLAH n SUKU PERTAMA PADA GENERALISASI BILANGAN FIBONACCI DENGAN METODE MATRIKS - Purnamayanti Purnamayanti; Thresye Thresye; Na'imah Hijriati (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2012)
Fibonacci numbers are defined as sequences of precise numbers is the sum of the previous two tribes. Binet in 1875 proposes an Fn formula capable of calculating the nth number of numbers it is faster without having to recalculate as much as n times, which then known as Binet formulas or formulas. The purpose of this study is to learn the formation of the Binet formula, forming a generalization of Binet formulas on Fibonacci numbers p-degree, look for the number of n tribes first in Fibonacci numbers p-degree with linear algebraic approach especially the use of matrices.